2021
DOI: 10.1007/s43452-021-00221-7
|View full text |Cite
|
Sign up to set email alerts
|

Seismic rocking effects on a mine tower under induced and natural earthquakes

Abstract: Recent research in engineering seismology demonstrated that in addition to three translational seismic excitations along x, y and z axes, one should also consider rotational components about these axes when calculating design seismic loads for structures. The objective of this paper is to present the results of a seismic response numerical analysis of a mine tower (also called in the literature a headframe or a pit frame). These structures are used in deep mining on the ground surface to hoist output (e.g. cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…, ω n are the cutting circular frequencies in the dispersion curve. To identify the participation factor 𝑁 𝑗 𝑚 , the energy flow density S𝑗 𝑚 naturally becomes the parameter to be prior determined, necessitating the determination of unknown free-field stresses and velocities as shown in Equations ( 16) and (19). For Rayleigh waves in the jth sublayer, the free-field velocities U𝑗 X (z, ω) and U𝑗 Z (z, ω) of the x = 0 cross-section can be easily acquired with the differential of the free-field displacements as…”
Section: Modal Participation Factormentioning
confidence: 99%
See 1 more Smart Citation
“…, ω n are the cutting circular frequencies in the dispersion curve. To identify the participation factor 𝑁 𝑗 𝑚 , the energy flow density S𝑗 𝑚 naturally becomes the parameter to be prior determined, necessitating the determination of unknown free-field stresses and velocities as shown in Equations ( 16) and (19). For Rayleigh waves in the jth sublayer, the free-field velocities U𝑗 X (z, ω) and U𝑗 Z (z, ω) of the x = 0 cross-section can be easily acquired with the differential of the free-field displacements as…”
Section: Modal Participation Factormentioning
confidence: 99%
“…18 Bońkowski et al demonstrated the contribution of the Rayleigh waves to mine towers and suggested their involvement in future calibrations of the seismic codes. 19 Meza-Fajardo et al concluded that the rocking motions associated with Rayleigh waves can trigger dominant responses of SSI systems and should be a necessary consideration for the structural design. [20][21][22][23] Alielahi et al also recommended considering Rayleigh waves in the design of soil-cavity interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies (e.g., Xia et al 2006; Yuen and Kuok 2010; Guéguen et al 2017;Astorga et al 2018) also con rmed the effects of environmental factors through mathematical statistical analyses. Other studies (e.g., Shan et al 2020;Bońkowski et al 2021) revealed a building's self-healing ability, where the building's resonant frequency drift due to earthquake events, environmental factors, or random forced vibrations could gradually return to its original level, although the recovery times of frequency drift could be considerably different with respect to different environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…found that the rotation rate derived from the translational array is smaller than that recorded by a rotational seismometer when the center of torsion is not located at the same location, which facilitates the judgment of the rotational center of the building. Bońkowski et al (2018Bońkowski et al ( , 2019Bońkowski et al ( , 2021 found that the bending moments of high slender towers are signi cantly affected by the rotational motion of the ground, although under a moderately intensive rotational earthquake. However, there are still many issues that need to be addressed, such as the characteristics of high-rise building rotation under environmental ambient noise and earthquakes and their differences and the impact of seismic rotational motion on asymmetric high-rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The large headframe is the core structure of a mine hoisting system, and also a highrise and hollow steel-framed building [1][2][3]. With the development of mine hoisting system towards large-scale, higher requirements are put on the structural design of the large headframe [4,5].…”
Section: Introductionmentioning
confidence: 99%